FAKTOR–FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN TAHUNAN PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2014) - Rika Maya Sari; Zulbahridar Zulbahridar; Azhari Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study was to examine the effect of profitability, laverage, size, age, and liquidity on the timeliness of the company annual financial reporting. Independent variables used in this study are profitability, laverage, size, age, and liquidity, while dependent variables in this study is the timeliness of the company annual financial reporting. The populations used in this study are all of maufacture compenies listed on IDX 2011-2014 where the total sample is used by 98 companies. The sampling thecnique in which the number of observation obtained this study was 392 (98x4). The method of analysis of this study using multiple regression analysis with help of softwere SPSS version 20,0. This study used classic assumption test composed of normality test , heteroskedasity test, autocorrelation test, and multi collinearity test. While hypothesis test is down with t test. The results of this study indicate that all independent variables are profitability, laverage, size, age, and liquidity affect the timeliness of the annual financial reporting on the level of significant (α) < 0,05. The coefficient of determination as big as 70,2 indicates that 70,2 % of the variations that occur in the timeliness of the annual financial reporting is affected by profitability, laverage, size, age, and liquidity while the rest of 29,8% were affected by other variabel that were not performed in this study.Keywords: Timelines, profitability, size company, age company, and liquidity.